Penambahan Vitamin C Dalam pakan dengan Dosis Berbeda Terhadap Pertumbuhan Dan Kelangsungan Hidup Lobster Air Tawar (Cherax quadricarinatus) - Badjuka, Dwi Andita; Koniyo, Yuniarti; Lamadi, Arafik (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
Freshwater Crayfish (Cherax quadricarinatus) is one of the flagship commodities in fisheries. Vitamin C is an essential nutrient to support the growth of C.quadricarinatus. this research aimed to determine the effects of the addition of vitamin C into artificial feed with different dosages. The tested animals were 120 Freshwater Crayfish juveniles with an average initial length of ± 4 cm and a weight of 3 grams. The water volume used was 10 liters/container. This rescarch was conducted for 43 days. The research method used was an experimental method with a completely randomized design (CRD), consisting of 4 treatments and 3 replications. Treatments A : Without vitamin C, treatments B: 250 mg/kg feed, treatments C: 300 mg/kg feed, treatments D: 350 mg/kg feed. The results showed no significant difference in length, weight, and survival rate, but there was a significant difference in the molting frequency with the best results in treatment D. The administration of vitamin C at a dosage of 350 mg/kg feed resulted in good growth in freshwater Crayfish juveniles with an average length of 1,27 cm an average weight of 1,29 grams, and a survival rate of 96.67%.